PENGARUH EKSPOR IMPOR KAKAO DAN KARET TERHADAP CADANGAN DEVISA DI INDONESIA - Mustafa Mustafa; Devi Andriyani (Jurnal Ekonomi Pertanian Unimal, 2020)
This study aims to analyze the effect of cocoa and rubber export imports on foreign exchange reserves in Indonesia. This study uses secondary data from 2005-2017 obtained from the Central Bureau of Statistics of Indonesia. The data analysis method used multiple linear regression models. The results partially show that cocoa and rubber export impors do not significantly influence the foreign exchange reserves in Indonesia. Simultaneous cocoa and rubber export imports have a positive and significant effect on foreign exchange reserves in Indonesia. The amount of influence is 0,9059 or 90,59% while the rest is influenced by other variables outside the model by 09,41%.